Nutritional and industrial relevance of particular Neotropical pseudo-cereals - Acuña Gutiérrez, Catalina Alejandra (2019)
Several pseudo-cereals (plants not belonging to the Poaceae family but with uses similar to those of the traditional cereals) of Neotropical origin have been cultivated and consumed since pre-Columbian times by indigenous communities. Nowadays, some of these crops are gaining the interest of consumers, because of their functional properties and convenience in case of particular medical conditions (like celiac disease). For the food industry sector, these pseudo-cereals offer the opportunity to develop new ingredients and products to reach these new markets, by promoting them as new health-beneficial alternatives. In this chapter, we focus on eight Neotropical pseudo-cereals (i.e., common bean, amaranth, quinoa, chia, chan, jícaro seeds, ojoche and the Andean lupine). For each one, some background on the origin/distribution and traditional importance has been included, followed by data on its nutrition relevance and consumption habits, and finalizing with recent discoveries in terms of its functional properties and possibilities for industrialization. Information available varies according to crop, having some, like the common bean, more relevance, tradition and are more widespread. Others are barely and only locally known, and the information available is more limited.